2003
DOI: 10.1111/j.1728-4457.2003.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and Distorted Sex Ratios in a Rural Chinese County: Culture, State, and Policy

Abstract: This article explores how gender bias in population policies interacts with local culture to reinforce distortions in sex ratios among infants and young children in rural China. It argues that population policies introduce new sources of inequality into local culture while, conversely, gender inequalities embedded in local culture influence formal population policy and practice. Applying an institutional approach to the study of an agricultural county in Jiangxi province, southeast China, the analysis identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…In her study of a single county in Jianxi Province in 2000, Murphy (2003) found the male/female sex ratio among children under five years to be no less than 1.27. She gave three possible reasons for this extremely high ratio, all based on an underlying preference for sons: female infanticide, the abandonment of girl babies, and sexselective induced abortions.…”
Section: Evidence Of Son Preferencementioning
confidence: 96%
“…In her study of a single county in Jianxi Province in 2000, Murphy (2003) found the male/female sex ratio among children under five years to be no less than 1.27. She gave three possible reasons for this extremely high ratio, all based on an underlying preference for sons: female infanticide, the abandonment of girl babies, and sexselective induced abortions.…”
Section: Evidence Of Son Preferencementioning
confidence: 96%
“…Established to combat escalating population growth that occurred during the pronatalist Mao Period (1949 to the 1970s), this regulation was instituted in 1979 and continues in a revised form to the present day. Due to a historical preference for sons to provide labor power and perform ancestral rites of worship, as well as expectations that they will care for their parents in old age (Greenhalgh & Winckler, 2005;Murphy, 2003), stringent Chinese fertility regulations have resulted in abortion, neglect, illegal abandonment, and even infanticide of both girls and children with special needs (Croll, 2000;Chu, 2001;Yong & Lavely, 2003). In the process, thousands of healthy girls-the majority of them second or third daughters in families that seek to bear a son (Johnson, 2004)-have become available for adoption.…”
Section: Adoption Of Chinese Childrenmentioning
confidence: 98%
“…Others have examined the role of son preference in slowing the transition to low fertility as couples bear children until they have sufficient boys (Arnold, Minja, & Roy 1998;Clark 2000;Das Gupta & Bhat 1997;Leone et al, 2003;Yount, Langsten, & Hill, 2000, among others). The advent of technology permitting prenatal sex selection has shifted the focus of scholars and policymakers to sex-selective abortion and consequent distorted sex ratios as manifestations of son preference (Arnold, Kishor, & Roy, 2002;Murphy, 2003;Oomman & Ganatra, 2002).…”
Section: Introductionmentioning
confidence: 99%